CATEGORY SHIFT ON TOURISM MAGAZINE FROM ENGLISH INTO INDONESIAN: A TRANSLATION STUDY - syahma, raisya (LPPM Universitas Dhyana Pura, 2024)
This study aims to analyze the category shifts found on tourism magazine. The qualitative descriptive method is used in this study to analyze the data. The source of the data was a tourism magazine of Api Bali English-Indonesian version. Data were collected on magazine from page 1-10. Theory of Catford (1965) regarding of category shifts was used to analyze the data. From the analysis found that there are 8 structure shift , include 6 structure shift changes word order, and 2 structure change the grammatical order, 2 class shift, 4 unit shit, and 4 of intra-system with the highest usage of category shift is structure shift with a total of 8.